The first fossil seed of Ampelopsis (Vitaceae) in South China - Xiang, Helanlin; Wu, Xinkai; Liu, Xiaoyan; Xu, Shenglan; Jin, Jianhua; Huang, Luliang (Frontiers in Ecology and Evolution, 2023)
Ampelopsis Michx. (Vitaceae) contains more than 30 species and is discontinuously distributed in Eurasia, North America, and Central America. China hosts an abundance of Ampelopsis species. Up to now, fossil records of Ampelopsis have been reported only from the Paleocene to Pleistocene of Europe, the Eocene to Pliocene of Asia, and the Eocene to Miocene of North America. Although Ampelopsis is abundant and widespread in China today, until now no fossils of Ampelopsis, apart from fossil seed from the Late Miocene of Yunnan, have so far been found there. In this study, a fossil seed of Ampelopsis japonica (Thunb.) Makino was recovered from the Upper Pleistocene of the Maoming Basin, Guangdong Province. It is the first Ampelopsis fossil found in South China. This finding shows that Ampelopsis was distributed in the low-latitudes of South China in the Late Pleistocene. Global cooling during the last glaciation might have led to the southward spread of the genus to the low-latitude areas of South China. According to the structural characteristics of our fossil, it was speculated that the aborted ovule, which are common in the fruits of extant Ampelopsis, had existed in this genus in the Late Pleistocene.